แนวทางพัฒนาการบริหารวิชาการโรงเรียนระดับประถมศึกษาสังกัดกรุงเทพมหานครตามแนวคิดคุณลักษณะความเป็นผู้ประกอบการ - สุภาวดี แซ่ด่าน (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
This research aims to 1) study the current and desirable conditions for academic management development in primary schools under Bangkok Metropolitan Administration based on the concept of entrepreneurship characteristics, 2) present the approaches for academic management development in primary schools under Bangkok Metropolitan Administration based on the concept of entrepreneurship characteristics. Using descriptive research methods. The sample group was 209 primary schools under the Bangkok Metropolitan Administration. 836 informants were consisting of school director, deputy director of academic affairs, head of department, and student. Data were collected using questionnaires and the appropriateness and feasibility assessment form. The data were analyzed by finding percentage, mean, standard deviation, PNImodified, Mode, and Content Analysis. The research results found that 1) the current state of academic administration in primary schools under Bangkok Metropolitan Administration was at a high level (M = 4.126). When considering academic administration, were found that school curriculum development was at the highest level (M = 4.165) and teaching activities had the lowest level (M = 4.108). Entrepreneurship characteristics moral and reliable were at the highest level (M = 4.295), and the lowest level was taking risks (M = 3.777). Desirable condition at the highest level (M = 4.705). Considering academic administration, organizing extra-curricular activities were at the highest level (M = 4.716) and measurement and evaluation have the lowest level (M = 4.700). Entrepreneurship characteristics, the result was the same as present state, moral and reliable were at the highest level (M = 4.779), and the lowest level was taking risks (M = 4.510). The priority needs of academic administration is teaching activities (PNImodified = 0.145) and the entrepreneurship characteristics are taking risks (PNImodified = 0.194). 2) the approaches for academic management development in primary schools under Bangkok Metropolitan Administration based on the concept of entrepreneurship characteristics consisted of 5 approaches as follows: (1) Change the teaching and learning management to develop learners to take risks, be creative, have imagination, and think innovatively by doing a Startup project, an integrated project between courses and the hands-on practice. (2) Develop media and learning resources that encourage learners to take risks and have confidence through providing new learning materials and Makerspace. (3) Improve the measurement and evaluation of learning in taking risks, patience and stability in the learner s emotions by establishing learners behavior indicators. (4) Transforming extra-curricular activities aimed at developing the learner s risk taking and have confidence in him/herself by organizing activities themselves focusing an community career promoting and able to enable participants to bring experience to further their career. (5) Develop a school curriculum that encourages learners to take risks, creative, have imagination, and think innovatively by defining the aim of the curriculum and learning contents in the courses.